PENGARUH PERBEDAAN KONSENTRASI TEPUNG DEKSTRIN DAN LEMAK DALAM PAKAN BUATAN TERHADAP BUANGAN AMONIAK JUVENIL UDANG WINDU (Penaeus monodon) - Pinandoyo Pinandoyo; Vivi Endar Herawati; Galih W H (Pena Akuatika Jurnal Ilmiah Perikanan Dan Kelautan, 2017)
This purpose of this studyis to determinethe optimizationof the use of dextrin on shrimp feedin pellet form to reveal the value of protein efficiencyratio (PER), the efficiencyof feed utilization(EPP), the relative growth rate(RGR) andsurvival rate(SR) of juveniletiger shrimp(P. monodon). experimental method with used complete randomized design(CRD) 4 treatmentsandt 3 plications. Feedgiven4 timesa dayat 08.00, 13.00, 17.00 and23:00as much as 8% of theweight ofthe shrimpbiomass.TreatmentA,B, C, andDareapplied with a crumble shaped of artificial feedand different concentration of dextrin such as 19.98; 17.98; 15.98, and 13.98%. The variablestested wereRGR, SR, FCR, PER, EPP.The results showedthat the paste shape of artificialfeed with different proteinsconcentration give ahigh significantly different to theSGR, PER, EPP, and give not significantly differenttoSR of juveniletiger shrimp. RGRvalue(%), C (4.22 0.38), B (3.26 0.04), A(2.790.25)andD(2.610.23).SRvalues(%) is B(88.89±1.92), C(88.89±5.09), D(86.67±3.33) andA (85.56 ±3.85). PERvalue(%),C (1,21±0,02), B (1,12±0,04), A (1,06±0,04), and D(0,96±0,02) .EPPvalues(%), C (36.43 ±0.66), B (35.97 ±1.18), A (33.98 ±1.39) andD(28.85 ±0.53).Keywords: Dextrin, growth, feedefficiency, survival, Penaeusmonodon